Single nucleotide variant counts computed from RNA sequencing and cellular traffic into human kidney allografts. Issue 10 (15th May 2018) - Thareja, Gaurav; Yang, Hua; Hayat, Shahina; Mueller, Franco B.; Lee, John R.; Lubetzky, Michelle; Dadhania, Darshana M.; Belkadi, Aziz; Seshan, Surya V.; Suhre, Karsten; Suthanthiran, Manikkam; Muthukumar, Thangamani
Abstract : Advances in bioinformatics allow identification of single nucleotide polymorphisms (variants) from RNA sequence data. In an allograft biopsy, 2 genomes contribute to the RNA pool, 1 from the donor organ and the other from the infiltrating recipient's cells. We hypothesize that imbalances in genetic variants of RNA sequence data of kidney allograft biopsies provide an objective measure of cellular infiltration of the allograft. We performed mRNA sequencing of 40 kidney allograft biopsies, selected to represent a comprehensive range of diagnostic categories. We analyzed the sequencing reads of these biopsies and of 462 lymphoblastoid cell lines from the 1000 Genomes Project, for RNA variants. The ratio of heterozygous to nonreference genome homozygous variants (Het/Hom ratio) on all autosomes was determined for each sample, and the estimation of stromal and immune cells in malignant tumors using expression data (ESTIMATE) score was computed as a complementary estimate of the degree of cellular infiltration into biopsies. The Het/Hom ratios ( P = .02) and the ESTIMATE scores ( P < .001) were associated with the biopsy diagnosis. Both measures correlated significantly ( r = .67, P < .0001), even though the Het/Hom ratio is based on mRNA sequence variation, while the ESTIMATE score uses mRNA expression. Het/Hom ratio and the ESTIMATE score may offer unbiased and quantitative parameters for characterizing cellular traffic into human kidney allografts. Abstract : The ratio of heterozygous to nonreference genome homozygous single nucleotide variants computed from human kidney allograft RNA‐sequencing data offers an unbiased and quantitative parameter for characterizing cellular traffic into the kidney allografts.